The quantum confined Stark effect in N-doped ZnO/ZnO/N-doped ZnO nanostructures for infrared and terahertz applications - Pornsawan Sikam (2020)
© 2020 IOP Publishing Ltd. The terahertz (THz) frequency range is very important in various practical applications, such as terahertz imaging, chemical sensing, biological sensing, high-speed telecommunications, security, and medical applications. Based on the density functional theory (DFT), this work presents electronic and optical properties of N-doped ZnO/ZnO/N-doped ZnO quantum well and quantum wire nanostructures. The density of states (DOS), the band structures, effective masses, and the band offsets of ZnO and N-doped ZnO were calculated as the input parameters for the subsequent modeling of the ZnO/N-doped ZnO heterojunctions. The results show that the energy gaps of the component materials are different, and the conduction and valence band offsets at the ZnO/N-doped ZnO heterojunction give type-II alignment. Furthermore, the optical characteristics of N-doped ZnO/ZnO/N-doped ZnO quantum well were studied by calculating the absorption coefficient from transitions between the confined states in the conduction band under the applied electric field (Stark effect). The results indicate that N-doped ZnO/ZnO/N-doped ZnO quantum wells, quantum wires, and quantum cascade structures could offer the absorption spectrum tunable in the THz range by varying the electric field and the quantum system size. Therefore, our work indicates the possibility of using ZnO as a promising candidate for infrared and terahertz applications.